The impact of state workplace protections on socioeconomic outcomes of IPV survivors - Marçal, Katherine E. (Journal of family violence, 2024)
Purpose: Intimate partner violence (IPV) can have devastating socioeconomic costs for survivors. Several policies exist to support survivors’ socioeconomic stability, but little research examines their impacts. The present study investigates whether three state-level workplace protections for IPV survivors – (1) right to reasonable accommodations; (2) confidentiality; and (3) protection from discharge for abuse-related work disruptions – are associated with increased employment and housing stability in a sample of mothers who have experienced IPV. Method: Data on survivors came from the Fragile Families and Child Wellbeing Study; the analytic sample was limited to mothers who had experienced IPV. State policy protections were compiled and merged with Fragile Families data in order to indicate which mothers lived in states with certain protections. Three hierarchal logistic models that nested women (N = 1,296) within states (N = 37) tested associations of living in a state with each of the protective policies with employment status and housing hardship. Results: All three policies were associated with increased likelihood of employment, but none related with reduced risk for housing hardship. Conclusions: Reasonable accommodations, privacy protection, and protection from discharge help survivors keep their jobs. State efforts to implement widespread protections for IPV survivors offer promise for promoting socioeconomic stability, but additional policies are needed to promote stable housing.